Sustainable valorization of halophytes from the Mediterranean area: a comprehensive evaluation of their fatty acid profile and implications for human and animal nutrition - Vizetto-Duarte, C (2020)
Halophytic plants can provide an economical and environmentally sustainable source of products for human and animal feeding, in the context of the increase of worldwide emergent semi-arid landscapes. This work reports a comprehensive evaluation of the qualitative and quantitative composition of fatty acids (FA) of nineteen Mediterranean halophytes collected in southern Portugal, with the purpose of establishing their possible uses as food and feed. For FA determination, lipids and free FA were converted to the corresponding fatty acid methyl esters (FAME) and analyzed by GC-MS. Beta maritima had the highest FAME levels (7.3 mg/g DW) while Suaeda vera had the lowest content (1.0 mg/g DW). The most common saturated fatty acid (SFA) across all studied species was palmitic acid. The most prevalent monounsaturated fatty acid (MUFA) was oleic acid. Polyunsaturated fatty acids (PUFA) levels were led by linoleic acid. Less common FAMEs were also detected, namely eicosadienoic and hexadecatrienoic acids. Cotula coronopifolia, Phragmites australis and Suaeda vera displayed the best FA nutritional profiles. These species also showed bioactivities relevant for both human and animal health according to the literature and thus, collectively with this study, they could be further explored as food and feed.